2022
DOI: 10.13057/biodiv/d230602
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bird species in Pangheotan grassland and Mount Masigit Kareumbi Hunting Park, West Java, Indonesia

Abstract: Abstract. Withaningsih S, Parikesit, Rakha. 2022. Diversity of bird species in Pangheotan grassland and Mount Masigit Kareumbi Hunting Park, West Java, Indonesia. Biodiversitas 23: 2790-2798. The diversity of bird species is often used as an indicator of the ecosystem balance of an area. One of the efforts to preserve and protect the diversity of bird species is made by fostering habitat in the Pangheotan I Grassland (Kebun Rumput Pangheotan, hereinafter Pangheotan grassland) of PT. Perkebunan Nusantara (PTPN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The closer the food source, the shorter it takes bees to gather food. Likewise, the energy needed to go back and forth to visit the food source became more efficient [7].…”
Section: >2 M <10mentioning
confidence: 99%
See 3 more Smart Citations
“…The closer the food source, the shorter it takes bees to gather food. Likewise, the energy needed to go back and forth to visit the food source became more efficient [7].…”
Section: >2 M <10mentioning
confidence: 99%
“…It followed the statement from researcher [3], who reported that most stingless bee species reared in Jambi and South Sumatra were H. itama. The rearing box shape specificity of honey bees and placement depended on honey bee species [7]. In Figure 5d, the stacked boxes were usually used to keep small stingless bees, such as Tetragonula laeviceps, while the large ones were placed separately (Figures 5c and 5e).…”
Section: Honey Bee Visitation Time and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hutan buru, juga dikenal dengan taman buru, merupakan satu tipe hutan konservasi yang membolehkan kegiatan berburu. Kegiatan berburu ini adalah kegiatan wisata yang diperuntukkan bagi wisatawan tertentu (Withaningsih et al, 2022). Berburu pada taman buru juga bermaksud untuk mengendalikan populasi hewan dan hama.…”
Section: A Latar Belakangunclassified